Optimization of Complex Methods Treatment of Inflammatory Periodontal Diseases - Mirzakulova Lola Tohirovna; Burxonova Zarafruz Qobilovna (Genius Journals, 2023)
Periodontal diseases are currently among the most common in dental practice and affect patients of all age groups. The structural and functional state of the periodontal, like any mucous membrane, depends on the activity of the hormonal background of the body. As practice shows, bacterial microflora is the root cause of periodontal diseases only in 20% of cases, mainly microorganisms play a secondary aggravating, but not causal function.
Keywords: inflammatory periodontal diseases; chronic generalized periodontitis; biofilm; vector therapy